THE IMPORTANCE OF ENGLISH FOR SPECIFIC PURPOSES BASED ON THE ENGINEERING STUDENTS’ PERCEPTIONS - Brilianti, Dani Fitria; Rokhim, Abdul (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2023)
English for Specific Purposes (ESP) is garnering significant attention and anticipation for its contribution to the teaching and learning process at the Polytechnic of Road Transportation Safety in Indonesia. Consequently, this study offers valuable insights into the perceptions of cadets at a vocational college regarding the significance of the ESP course within the transportation engineering program. Specifically, this paper aims to explore the cadets' perspective on the role of ESP in their future careers. By conducting a qualitative descriptive study, four types of questionnaires were administered to a total of ninety second-year cadets who are pursuing a major in transport engineering. The findings reveal that the cadets/students recognize the importance of ESP as a crucial subject that supports their future employment prospects. Moreover, they acknowledge the appropriate allocation of time to ESP within their curriculum, recognizing its necessity for their academic success and eventual career advancement. Understanding the importance of ESP is crucial for cadets aspiring to work in the industry. Cadets must have a strong motivation to learn and familiarize themselves with core engineering concepts in order to establish themselves as competitive engineers on a global scale.